MEMBERIKAN PEMAHAMAN TENTANG PENGHAPUSAN ESELON III DAN IV PADA PEGAWAI DINAS LINGKUNGAN HIDUP KABUPATEN BLORA - Purwanto, Adi; Nurati, Dian Esti (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
Bureaucracy has a heavy duty to implement the government’s vision and mission. Therefore, reliable, integrated, honest, capable, and high-motivation personnel are required. Bureaucratic reform should be implemented using master plan of human resource with massive bureaucratic simplification, because the existing bureaucratic is too long. The position of ASN (State Civil Apparatuses) will be based on functional position only, requiring more skill and competency. In bureaucratic reform, ASN faces a problem, that is, government’s plan to remove structural post of echelons III and IV. The government wants to break the too long procedure in bureaucracy and expect to accelerate decision making and to accelerate public service when bureaucratic reduction is implemented. There are some solutions to the problem discussed, among others: a. amending ASN Law, particularly related to ASN position and ASN management; b. reorganizing the institutional structure (central and regional) in order to adapt to the bureaucratic function needed; c. reinforcing the integrated carrier building for ASN personnel emphasizing more on functional position; d. the establishment of work relation pattern and inter-function coordination that can project the quick and simple bureaucratic working system; changing ASN personnel’s mindset into work professionalism-orientation based on merit system. Internal expectation in the discussion resulting from this socialization includes: a) Regency Government gives inadequate socialization to ASNs, so that they have not understood completely the echelon removal policy; b) the echelon officials approaching pension age can accept the echelon removal policy; c) the young and productive echelon officials prefer structural position because they get more facilities and wellbeing than they do in functional position; d) potential staffs often attend education and training, have visionary perspective, and prefer functional position because they can get position promotion more quickly impacting on the increasing income; e) the staffs without structural position prefer functional position because their pension age can be up to 60 years. Recommendation and expectation to be obtained from this socialization is that all ASNs in DLH Blora will acquire complete information on echelon removal plan and keep their working spirit